Application of AI in Halal Marketing: Navigating the Ethical Crossroads - Md Mahfujur Rahman; Abdullah Al Mahi; Md Abu Zarif Hossian (West Science Interdisciplinary Studies, 2024)
This article examines the intricate process of applying Artificial Intelligence (AI) in the Halal marketing landscape, situated at a critical ethical crossroads. It explores the integration of AI technologies within Halal marketing strategies, emphasizing the importance of aligning with ethical, legal, and Islamic principles. Highlighting AI's potential to transform consumer engagement and trust, the paper advocates for a proactive approach in developing AI applications that respect Islamic values, consumer privacy, and fairness. It calls for collaborative efforts in crafting regulatory frameworks and ethical AI algorithms that are congruent with Halal standards, thus ensuring technology acts as a catalyst for ethical growth and integrity within the industry. The discussion underscores the dual aspects of opportunities and challenges presented by AI, urging a balanced embrace of technological advancements while safeguarding Islamic ethical and legal norms to foster the ethical expansion of the Halal industry globally.